2020
DOI: 10.1093/cid/ciaa214
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of 3 Clinical Criteria for Sepsis (Quick Sequential Organ Failure Assessment, Systemic Inflammatory Response Syndrome, and National Early Warning Score) With Respect to Short-term Mortality in Allogeneic Hematopoietic Cell Transplant Recipients With Suspected Infections

Abstract: Background Sepsis, a life-threatening immunological response to an infection, disproportionality affects allogeneic hematopoietic cell transplant (HCT) recipients and is challenging to define. Clinical criteria that predict mortality and intensive care unit endpoints in patients with suspected infections (SI) have been adopted in sepsis definitions, but their predictive value among immunocompromised populations is largely unknown. Here, we evaluate three criteria among allogeneic HCT recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 28 publications
(22 reference statements)
4
28
0
Order By: Relevance
“…11 This difference is likely driven by our decision to evaluate potential infections (ie, all blood cultures) instead of the commonly used suspected infections (ie, body fluid cultures collected within a specific antibiotic time epoch) as well as missingness frequency differences (suspected infection study temperature missingness, 6%; temperature missingness in this study, 35%). 11,18 While examining PBIs likely contributed to our large amount of missingness and meant we included some cultures in the absence of clinical suspicion of infection (ie, surveillance cultures), we evaluated PBIs rather than suspected infections because our primary end point required blood culture confirmation, and we wanted our tools to inform antibiotic treatment use rather than estimate disease escalation among patients already receiving antibiotic treatment. 34,37 To ensure our tools were not biased toward surveillance cultures, we performed a sensitivity analysis excluding surveillance cultures and found that neither C-SHBSL nor SHBSL performed meaningfully different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This difference is likely driven by our decision to evaluate potential infections (ie, all blood cultures) instead of the commonly used suspected infections (ie, body fluid cultures collected within a specific antibiotic time epoch) as well as missingness frequency differences (suspected infection study temperature missingness, 6%; temperature missingness in this study, 35%). 11,18 While examining PBIs likely contributed to our large amount of missingness and meant we included some cultures in the absence of clinical suspicion of infection (ie, surveillance cultures), we evaluated PBIs rather than suspected infections because our primary end point required blood culture confirmation, and we wanted our tools to inform antibiotic treatment use rather than estimate disease escalation among patients already receiving antibiotic treatment. 34,37 To ensure our tools were not biased toward surveillance cultures, we performed a sensitivity analysis excluding surveillance cultures and found that neither C-SHBSL nor SHBSL performed meaningfully different.…”
Section: Discussionmentioning
confidence: 99%
“…FHCRC guidelines during the study have been described elsewhere. 11 Briefly, cultures were recommended for patients with fevers, and surveillance cultures were recommended weekly or biweekly for patients receiving high-dose glucocorticoids (ie, >0.5 mg/kg). Levofloxacin was used as the primary antibiotic prophylaxis agent during neutropenic periods while patients with neutropenic fever received empirical therapy with ceftazidime, cefepime, or meropenem.…”
Section: Prophylaxis and Culture Collection Guidelinesmentioning
confidence: 99%
“…[20][21][22] Systemic inflammatory response syndrome (SIRS) is often used to predict infection or septic shock. [23][24][25][26][27] However, many of these scores include laboratory results and are used primarily for specific patients, limiting their value in emergency triage. However, general early warning scores, such as the MEWS and NEWS, are based only on readily available parameters, and thus have a good range of applicability.…”
Section: Discussionmentioning
confidence: 99%
“…The early recognition of sepsis and its severity are important for appropriate treatment, improving outcomes, and reducing costs [4]. Therefore, many screening tools have been proposed to identify disease severity, including the SOFA, qSOFA, Acute Physiology and Chronic Health Evaluation, Multiple Organ Dysfunction Score (MODS), National Early Warning Score (NEWS), and CURB-65 (confusion, urea > 7 mmol/L, respiratory rate ≥ 30/minute, low systolic [< 90 mmHg] or diastolic [≤ 60 mmHg] blood pressure, and age ≥ 65 years) [9][10][11].…”
Section: Discussionmentioning
confidence: 99%